Does Identity Incompatibility Lead to Disidentification? Internal Motivation to Be a Group Member Acts As Buffer for Sojourners from Independent Cultures, Whereas External Motivation Acts As Buffer for Sojourners from Interdependent Cultures - Matschke, Christina; Fehr, Jennifer (Frontiers in Psychology, 2017)
Most individuals possess more than one relevant social identity, but these social identities can be more or less incompatible. Research has demonstrated that incompatibility between an established social identity and a potential new social identity impedes the integration into the new group. We argue that incompatibility is a strong risk factor for disidentification, i.e., a negative self-defining relation to a relevant group. The current research investigates the impact of incompatibilities on disidentification in the acculturation context. We propose that incompatibility between one’s cultural identities increases the disidentification with the receiving society. It has, however, been shown that the motivation to be a group member serves as a buffer against negative integration experiences. Moreover, research from the intercultural domain has shown that intrinsic and extrinsic motivation has specific effects for members of cultures that differ in self-construal. In a European sample of High school exchange students (Study 1, N = 378), it was found that incompatibility was positively related to disidentification, but only for less (but not more) intrinsically motivated newcomers. In an Asian sample of international university students (Study 2, N = 74), it was found that incompatibility was also positively related to disidentification, but only for less (but not more) extrinsically motivated newcomers. Thus, the findings demonstrate that the effect of incompatibility between social identities on disidentification can be buffered by motivation. The results suggest that, depending on cultural self-construal, individuals have different resources to buffer the negative effect of incompatibility on the social identity.